Senescent cell reduction does not improve recovery in mice under experimental autoimmune encephalomyelitis (EAE) induced demyelination - Zeeba Manavi; George S. Melchor; Meghan R. Bullard; Phillip S. Gross; Shinjini Ray; Pankaj Gaur; Maryna Baydyuk; Jeffrey K. Huang (Journal of Neuroinflammation)
Abstract Multiple sclerosis (MS) is a chronic inflammatory disease of the central nervous system (CNS) characterized by immune cell-driven demyelination and progressive neurodegeneration. Senescent cells (SCs) have recently been observed in chronic MS lesions indicating their possible involvement in disease progression. However, the role of SCs and the potential therapeutic benefit of their reduction through senolytic therapy remains to be determined in experimental autoimmune encephalomyelitis (EAE), a widely used preclinical model of MS. Here, we show that senescent-like myeloid cells accumulate in the spinal cord parenchyma and meninges in mice after myelin oligodendrocyte glycoprotein (MOG33–55) EAE induction. Treatment with the senolytic cocktail, Dasatinib and Quercetin (DQ), effectively reduces the senescent-like myeloid cells, but this does not translate into improved clinical outcomes in EAE mice. Increasing DQ dosage or using INK-ATTAC transgenic mice also failed to ameliorate EAE severity. Additionally, histopathological analysis shows no significant differences in demyelination or axonal degeneration between treated and control groups. Our findings indicate that senescent-like myeloid cells are present in an immune-mediated demyelinating model of MS and can be reduced through senolytic therapy with Dasatinib and Quercetin. However, their reduction through DQ does not significantly impact inflammation or recovery, suggesting that the therapeutic potential of senolytics as disease-modifying drugs in MS may be limited.